Minimum Alveolar Concentration-Awake of Sevoflurane is Decreased in Patients with Parkinson’s Disease: An Up-and-Down Sequential Allocation Trial - Yang C (Dove Medical Press, 2021)
Chengwei Yang,1,* Fang Kang,1,* Wenjun Meng,1 Meirong Dong,1 Xiang Huang,1 Sheng Wang,1 Zhiyi Zuo,2 Juan Li1 1Department of Anesthesiology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, People’s Republic of China; 2Department of Anesthesiology, University of Virginia, Charlottesville, Virginia, USA*These authors contributed equally to this workCorrespondence: Zhiyi ZuoDepartment of Anesthesiology, University of Virginia, Charlottesville, Virginia 22908, USAEmail zz3c@virginia.eduJuan LiDepartment of Anesthesiology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei 230036, People’s Republic of ChinaEmail huamuzi1999@163.comBackground: An increasing number of patients with Parkinson’s disease (PD) will have surgery under general anesthesia. A previous study demonstrated that propofol requirement for inducing unconsciousness in PD patients was lower than that in non-PD (NPD) patients. However, the requirement of inhaled anesthetics in PD patients has not been clarified. The aim of this study was to investigate the minimum alveolar concentration-awake (MACawake) of sevoflurane in patients with PD compared to NPD patients.Patients and Methods: The current study is an up-and-down sequential allocation trial. The initial end-tidal concentration of sevoflurane (CETsevo) was estimated by the response of the previous patient to verbal command using the Dixon’s up-and-down method. The first patient in each group received CETsevo at 1%, and the step size between patients was 0.2%.Results: Forty-one patients including 20 PD patients and 21 NPD patients were enrolled. Patients’ characteristics and arterial blood gas parameters (except blood sodium) were comparable between two groups. The MACawake of sevoflurane estimated by the Dixon’s up-and-down method in PD patients (0.47% ± 0.08% [Mean ± S.D.]) was significantly lower than that in NDP patients (0.64% ± 0.10%) (P=0.003). The estimated difference in means was 0.17% (95% CI, 0.10– 0.24%). Probit analysis showed that the MACawake of sevoflurane in PD and NPD patients was 0.49% (95% CI, 0.42– 0.57%) and 0.67% (95% CI, 0.59– 0.76%), respectively. The relative median potency was 0.73 (95% CI, 0.38– 0.94).Conclusion: Patients with PD exhibit a significantly lower MACawake of sevoflurane compared with NPD patients. Clinicians should avoid an overdose of sevoflurane in patients with PD.Trial Registration: Registered at ChiCTR1900026956.Keywords: Parkinson’s disease, sevoflurane, the minimum alveolar concentration-awake